Female genital mutilation: a systematic review of research on its economic and social impacts across four decades - Emmanuel Kabengele Mpinga; Aurélie Macias; Jennifer Hasselgard-Rowe; Ngianga-Bakwin Kandala; Tshimungu Kandolo Félicien; Henk Verloo; Ngoyi K. Zacharie Bukonda; Philippe Chastonay (Taylor & Francis Group, 2016)
Background: Global efforts to end female genital mutilation (FGM) have intensified in recent decades because of the rising awareness that such a practice is an act of extreme violence against women and girls. Articles on FGM have been published highlighting the combined efforts of international and non-governmental organizations, governments, as well as religious and civil society groups to end the practice. However, the consequences of this research are not well known, and it seems that the socioeconomic aspects of the practice are underreported. Objective: This review aims to characterize over a 40-year period the scientific output on the consequences of FGM in African countries, the most affected region known for the high prevalence of FGM, and review data on the socioeconomic consequences of the practice. Design: A systematic review of literature was done, looking at the following databases: PubMed, Embase, CINAHL, BDSP, Web of Science, PsycINFO, FRANCIS, Sociological Abstracts, WHOLIS, RERO, and SAPHIR. The analysis was limited to articles concerning the African continent, published in English and French, from January 1, 1972, to December 31, 2011. Results: One hundred ninety-eight articles were reviewed. More than half of the articles were published during the last decade of the study period. The majority of papers were published in biomedical journals (64.1%). Most studies looked at Africa as a region (33.3%). Nigeria was the single country most investigated (19.2%), followed by Egypt (10.6%). Most first authors were affiliated to non-African countries (60.6%): among them 21.2% were US-based, 4% were from African institutions, and 16.2% from Nigeria. The medical and psychological consequences (51.5%) and the prevalence and ethics of the practice (34.4%) were the most frequently investigated topics. The socioeconomic consequences were addressed in a minority of the papers (14.1%): they were classified into direct economic consequences (2.5%), school attendance (1%), marriageability (2%), sexual and marital consequences (3.5%), fertility (2.5%), domestic violence (1%), and discrimination (1.5%). Conclusions: The publication of articles on the consequences of FGM is increasing, but there is little research on the socioeconomic consequences of the practice. More scientific data focusing on this dimension is necessary to strengthen prevention, advocacy, and intervention campaigns.